Analisis Tekanan Klien dan Etika Profesi Auditor dalam Menjaga Independensi: Systematic Literature Review (Lembaga Pengembangan Kinerja Dosen, 2026)
This study examines the relationship between client pressure and auditor independence, with professional ethics serving as an internal control mechanism. The main problem arises from the phenomenon of declining auditor objectivity caused by economic pressure and close relationships with clients. Using a Systematic Literature Review (SLR) method guided by the PRISMA 2020 framework, a total of 215 peer-reviewed articles are initially identified from major academic databases, including Emerald Insight, Taylor & Francis, MDPI, PLOS ONE, and OJS SINTA 1-2. After rigorous screening and critical appraisal using CASP, 25 articles meet the inclusion criteria and are subjected to a comprehensive synthesis. The findings indicate that client pressure has a negative influence on auditor independence, while professional ethics strengthens auditors' commitment to maintaining objectivity. Cross-study comparisons analysis demonstrates that variations in the impact of client pressure across countries depend on the robustness of regulatory frameworks and the ethical culture within each jurisdiction. This research extends the application of Agency Theory by integrating internal and external determinants. The findings emphasize the importance of strengthening ethical culture within public accounting firms and implementing auditor rotation policies to uphold independence. This study is limited to prior quantitative research; therefore, future studies are recommended to integrate the variable of professional skepticism as a moral and cognitive control mechanism to enrich the understanding of auditor independence and behavioral dynamics.